SANKSI /PIDANA KERJA SOSIAL, TELAAH DOUBLE TRACK SYSTEM (MONO-DUALISTIK/DAAD-DAADER STRARFTRECHT) - Firmansyah,Riska Amalia Armin (Madani Legal Review, 2021)
This study aims to determine the concept of the double track system and its relation to social work crimes. This study uses a normative approach, data analysis is carried out using descriptive-qualitative analysis. The findings obtained from this study, among others. double track system or a 2 (two) track system, which recognizes the equality between criminal sanctions and action sanctions by looking at the fact that the elements of reproach/suffering through criminal sanctions and elements of coaching through action sanctions are equally important. Meanwhile, related to social work crime, it is associated with the concept of a double track system, which can be applied to 2 (two) aspects, namely non-litigation, that the case is resolved outside the court by applying social work sanctions and coaching, while litigation uses the term social work crime by modifying it in the form of working witnesses. which has several benefits such as fostering a social spirit, an event for socialization and an arena for building emotional relationships between the community and the community and the community with law enforcement as well as for the welfare of the community because the target is the economically disadvantaged